2013
DOI: 10.1074/jbc.m112.423756
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Methylome Analysis Reveals Widespread Functional Hypomethylation during Adult Human Erythropoiesis

Abstract: Background: Not much is known about epigenomic changes during the differentiation of human stem cells into mature enucleated red cells. Results: Methylome analysis during human erythropoiesis revealed that global hypomethylation occurs during this process and correlates with transcriptomic changes. Conclusion: Integrative analysis also allowed us to identify novel regulatory areas of the genome. Significance: Progressive functional hypomethylation during human erythroid differentiation changes the current para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
47
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 25 publications
7
47
0
Order By: Relevance
“…Moreover, according to a recent study, methylation is most relevant at the HSC level but less so after lineage commitment [11]. As determined using Dnmt3a −/− and Dnmt3b −/− HSCs, de novo methylation is important for HSC renewal but not for differentiation [12]; this notion is further supported by a recent study examining the differentiation of CD34 + cells into reticulocytes that compared early and late erythroid progenitors, revealing progressive hypomethylation to be the predominant change in DNA methylation [13]. Thus, DNA demethylation is an essential epigenetic mechanism for erythroid differentiation programs in both ESCs and HSCs.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Moreover, according to a recent study, methylation is most relevant at the HSC level but less so after lineage commitment [11]. As determined using Dnmt3a −/− and Dnmt3b −/− HSCs, de novo methylation is important for HSC renewal but not for differentiation [12]; this notion is further supported by a recent study examining the differentiation of CD34 + cells into reticulocytes that compared early and late erythroid progenitors, revealing progressive hypomethylation to be the predominant change in DNA methylation [13]. Thus, DNA demethylation is an essential epigenetic mechanism for erythroid differentiation programs in both ESCs and HSCs.…”
supporting
confidence: 64%
“…However, regions outside of the promoters, as well as non-CpG island loci, are also very important for transcriptional regulation [16,17]. For example, a study examining erythropoiesis from CD34 + stem/hematopoietic cells revealed preferential progressive hypomethylation in gene bodies, intergenic regions and CpG shores; moreover, gene body hypomethylation was associated with decreased gene expression, in contrast to the effects of hypomethylation at promoters [13]. The true role of methylation changes in different genomic contexts must still be explored, taking into account numerous hypomethylation events -particularly at distinct differentiation stages.…”
mentioning
confidence: 99%
“…For instance, it was recently shown that erythroid differentiation is accompanied by functional demethylation of essential erythropoietic genes, including GATA1 (6,55). In addition, maintenance of HSC programs and prevention of activation of differentiation programs are controlled by DNA methylation (8).…”
Section: Figurementioning
confidence: 99%
“…DNA methylation is thought to provide a chemically stable mark that serves to initiate and reinforce these cell fate decisions. 2 Large-scale methylation studies of specific lineage pathways have been performed on differentiating erythroid, 3,4 T lymphocyte, 5,6 B lymphocyte, 7 and myeloid 4 cells. These important developmental studies reveal insights into the regulation of cell fate decisions but also serve as a potential source of biomarkers that help characterize different immune compartments during the immune response.…”
Section: Introductionmentioning
confidence: 99%